AN ANALYSIS OF TEACHER ASSESSMENT ON STUDENTS IN GOOGLE MEETING GRADING SYSTEM AT THE SECOND GRADE MAN BANTAENG - Nurul Hidayati; Erwin Akib; Muhammad Asrianto Setiadi (FKIP Unismuh Makassar, 2022)
This research aimed to find out how does the teacher assess students’ English learning achievement using Google Meeting Application at Second Grade MAN Bantaeng.This research used a descriptive qualitative method,the instruments used observation and interview. The observation used to observed the English teacher and the interview used to found How does the teacher assess students’ English learning achievement using Google Meeting Application.The subject of this research is teacher who teaching English using Google Meeting at second grade MAN Bantaeng.The results of this study show that teachers use speaking tests to assess students' English learning performance in the Google Meeting app. Teachers evaluate students' English learning performance through oral examinations. Students join Google Meetings one by one, and teachers then ask questions directly on daily exams or final exams. Teacher evaluations of the Google Meet Student Performance App show that students' English skills can improve after passing the Google Meeting app test. Students can respond well to questions posed by teachers.